2011
DOI: 10.1093/hmg/ddr338
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimethamine inhibits adult polycystic kidney disease by modulating STAT signaling pathways

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a commonly inherited disorder mostly caused by mutations in PKD1, encoding polycystin-1 (PC1). The disease is characterized by development and growth of epithelium-lined cyst in both kidneys, often leading to renal failure. There is no specific treatment for this disease. Here, we report a sustained activation of the transcription factor signal transducer and activator of transcription 3 (STAT3) in ischemic injured and uninjured Pkd1 knockout polycystic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
147
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 43 publications
5
147
1
3
Order By: Relevance
“…Previous findings by us 4 and others 7,8 have demonstrated that STAT3 is strongly activated in renal cyst-lining cells in human ADPKD and several PKD mouse models, and suggested that STAT3 is a driving force for cyst growth. 9,11 However, the mechanism of STAT3 activation in renal cysts remained unknown.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Previous findings by us 4 and others 7,8 have demonstrated that STAT3 is strongly activated in renal cyst-lining cells in human ADPKD and several PKD mouse models, and suggested that STAT3 is a driving force for cyst growth. 9,11 However, the mechanism of STAT3 activation in renal cysts remained unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Altogether, these results suggest that the high levels of cAMP and SOCS3 in renal cystic cells should be expected to suppress JAK-dependent activation of STAT3. However, because STAT3 is clearly strongly activated in PKD, 4,7,8 this suggests that STAT3 activation in PKD is mediated by a JAK-independent pathway. To directly test this, we investigated the levels of activated JAK2 (P-Tyr 1007/1008 ) in two PKD mouse models.…”
Section: Regulation Of Stat3 Activity and Socs3 Expression Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we performed immunohistochemistry to analyze phospho-STAT3 (pSTAT3), phospho-CREB, phospho-AKT, phospho-ERK1/2, and LCN2 expressions, which have been shown to be involved in PKD. 18,[23][24][25][26][27][28][29][30][31][32][33] The clustered distribution of cysts in an iKsp-Pkd1 del,lox mouse that was treated with low-dose tamoxifen, unilateral nephrectomy, and DCVC and euthanized 6 months after tamoxifen treatment (clustering is shown in Figure 6A), indeed, cooccurred with increased expression of these proteins specifically near cysts or clusters of cysts ( Figure 6B). We quantified the number of cysts/clusters that showed this effect in renal sections at two different locations in the kidneys of seven other mildly affected mice.…”
Section: Evidence For a Cystic Snowball Effectmentioning
confidence: 91%